Bauran Pemasaran Lobster Air Tawar pada Kelompok Petani Agro Crayfish di Denpasar - JAYANTI, NI KETUT ADI; ANTARA, MADE; GINARSA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.2, April 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; text-align:justify; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT Marketing Mix of Crayfish on Agro Crayfish Farmers Group in Denpasar The purpose of this study was to determine the application of the marketing mix of crayfish, the obstacles faced, and the strategies in the implementation. This research is descriptive qualitative. Based on the result of research on Agro Crayfish Farmers Group found that the application of the marketing mix in terms of products which is products marketed crayfish includes crayfish for consumption, breeding and nursery transplant. Pricing method is a fixed price. Distribution is defined direct and indirect distribution. The promotion is done by personal selling. The obstacle in product is that many crayfish dies due to cannibalism which could be resolved by feeding regularly. The obstacle in price is when the feed price goes up while the company can’t raise the determined price, and to cope with it the company has to get the consumers understanding. The obstacle in distribution is that during delivery there are some crayfish without claws or even dead, and to resolve it the company needs to limit the amount of crayfish per box. The obstacle in promotion is that the promotion done to market the product is not yet maximum, and to overcome it the promotion should be adjusted to the targeted market. Keyword: Marketing Mix, Crayfish , Farmers Group